Simple renal cysts in the solitary kidney: Are they innocent in adult patients?. Issue 5 (May 2017) - Tatar, Erhan; Ozay, Emine; Atakaya, Mehmet; Yeniay, Pinar Kezban; Aykas, Ahmet; Okut, Gokalp; Yonguc, Tarik; Imamoglu, Cetin; Uslu, Adam
Abstract: In patients with a solitary kidney; residual renal volume is an important prognostic factor for kidney survival. At present, the impact of renal cysts on solitary kidney survival is not clear. The aim of this study is to examine the association of cysts on progression of renal failure in patients with a solitary kidney. Methods: This study included sixtyfive solitary kidney patients. The remaining kidneys after indication nephrectomy (IN) were evaluated with urinary system ultrasound. The primary outcome of the study is the progression of kidney failure during follow‐up which was defined as: 25% decrease in glomerular filtration rate (GFR) and / or the need for renal replacement therapy (RRT). Results: The mean age of the patients was 55 ± 14 years and mean follow‐up was 53 ± 27 months. Renal cysts were present in 30.7% of patients. 33.8 percent of patients had kidney disease progression and 10.7 % required RRT. Those with progressive disease were older (61 ± 13, 52 ± 14; P =  0.011), had lower baseline GFR (30 ± 11, 39 ± 18; P =  0.035), higher proteiuria (2.84 ± 0.58, 2.47 ± 0.57; P =  0.031) and frequently harboring cysts in the solitary kidney (52.3%, 20.4%; P =  0.006). Progression to kidney failure and RRT requirement in cases with or without renal cysts was (60% vs. 22%; P =  0.004) and (20% vs. 6.6%; P =  0.123), respectively. Acquired cysts in solitary kidney was independently associated with progression to kidney failure and RRT respectively (Exp(B) 3.173; P =  0.01 and Exp(B) 12.35; P =  0.04). Conclusion: Simple renal cysts in solitary kidney patients with impaired renal function is associated with poor renal outcome. Large‐scale studies are needed to clarify this issue. Summary at a Glance: Kidney function affect by simple cyst is not clear. The aim of this study is to examine the association of cysts on progression of renal failure in patients with a solitary kidney. This study included sixty five solitary kidney patients and the primary outcome is the progression of kidney failure during follow‐up with a 25% decrease GFR and / or the need for renal replacement therapy. Result showed that acquired simple cysts in solitary kidney was independently associated with progression to kidney failure and the need for renal replacement therapy.